2021
DOI: 10.3390/v13061130
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment and Validation of High-Throughput Sequencing for Grapevine Virus Diagnostics

Abstract: Development of High-Throughput Sequencing (HTS), also known as next generation sequencing, revolutionized diagnostic research of plant viruses. HTS outperforms bioassays and molecular diagnostic assays that are used to screen domestic and quarantine grapevine materials in data throughput, cost, scalability, and detection of novel and highly variant virus species. However, before HTS-based assays can be routinely used for plant virus diagnostics, performance specifications need to be developed and assessed. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…They can also be used for (post‐entry) quarantine testing to prevent the establishment of pests in a country or area (Candresse et al, 2014; Fox et al, 2019; Malapi‐Wight et al, 2021), and to monitor imported commodities from different countries to avoid potential risks for plant health (Abdelfattah et al, 2019). High‐throughput sequencing technologies have been evaluated as a generic method for virus and/or viroid detection in grapevine and fruit trees (Al Rwahnih et al, 2015; Rott et al, 2017; Soltani et al, 2021; Villamor et al, 2021). They have also been used for the identification of bacteria in the re‐emerging disease ‘acute oak decline’ caused by a polymicrobial complex (Denman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can also be used for (post‐entry) quarantine testing to prevent the establishment of pests in a country or area (Candresse et al, 2014; Fox et al, 2019; Malapi‐Wight et al, 2021), and to monitor imported commodities from different countries to avoid potential risks for plant health (Abdelfattah et al, 2019). High‐throughput sequencing technologies have been evaluated as a generic method for virus and/or viroid detection in grapevine and fruit trees (Al Rwahnih et al, 2015; Rott et al, 2017; Soltani et al, 2021; Villamor et al, 2021). They have also been used for the identification of bacteria in the re‐emerging disease ‘acute oak decline’ caused by a polymicrobial complex (Denman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By following these recommendations, a laboratory should be ready to apply HTS technologies and start their development, validation or verification (Soltani et al, 2021). For this purpose, a complementary publication (Massart et al, 2022) provides technical and management guidelines covering the process of implementation of HTS technologies in a research or diagnostics laboratory (selection, development, verification and validation).…”
Section: Introductionmentioning
confidence: 99%
“…4 and S1). This result confirmed that, despite the widespread use of wood pruned during wintertime as tissue for viral diagnosis in grapevine, it is always advisable to use different organs, such as leaves in the vegetative period, which accumulate higher levels of viruses and viroids than other tissues (Gasparro et al ., 2019 ; Shabanian et al ., 2020 ; Soltani et al ., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The "map multiple best matches" option was set to "Randomly", under which the reads will be mapped randomly to one of the best hits presenting equal scoring. A sample was considered positive by HTS if more than 10 reads were mapped to one of the BanMMV downloaded sequences [23].…”
Section: Bioinformatics Analysismentioning
confidence: 99%